Nutritional value and health implications of traditional foods and drinks consumed during Ramadan : A narrative review: Dietary Habits and Ramadan - Said, Ebada M; Emara, Mohamed; Soliman, Hanan; Zaher, Tarik; Elbatae, Hassan; Abdel-Razik, Ahmed; Tawfik, Salwa; Elnadry, Mohamed (Progress in Nutrition, 2022)
Ramadan is a holy month of fasting for Muslims all over the world. It obligates a type of intermittent fasting from down to sunset. In oriental countries, Ramadan is linked to special foods and drinks like ingestion of dried fruits e.g. dates, apricot, figs, raisins and nuts; drinks e.g. carob, tamarind, hibiscus, sobya, doum, lemon, and licorice; foods e.g. yoghurt, beans and sugar rich desserts (kunafa and qatayef).  Traditionally, these dietary habits are thought to improve vitality, but they were scarcely tested in scientific manner. Is there a health impact of oriental drinks and foods commonly used in Ramadan? This was the research question of this review.In our search strategy, we used these dietary elements as key words in; Cochrane library, Web  of  Science  (WoS), Ovid, Since Direct, Scopus,  Directory    of    Open    Access    Journals    (DOAJ), EbscoHOST,  ProQuest, Institute  for Scientific  Information  (ISI),  EBESCO, Midline/Pubmed, Egyptian knowledge bank (EKB), Google scholar, or Research Gate.  We review studies focusing the impact of each drink or food on health regardless fasting state. Studies focusing chemical structure or agricultural issues were not included.  Among the foods and drinks evaluated, ingestion of dried fruits (dates, apricot, figs, raisins), nuts, carob, tamarind, hibiscus, sobya, doum, lemon, yoghurt, beans, were found not only tolerable but also beneficial among healthy subjects and patients with chronic diseases.The intake of licorice and sugar enriched desserts (kunafa and qatayef) should carefully be revised for patients with hypertension and diabetes due to slat retaining effect and high sugar content respectively.